Final evaluation of the "Making Health Choices" advance care planning in aged care project. Issue 2 (1st June 2012) - Sjanta, R; Jackson, L; Fullam, R; Lewis, V; Silvester, W
Abstract : Published literature suggests that advance care planning (ACP) activity in aged-care homes is inconsistent and often of poor quality. There are few published reports of the effectiveness of formal training and implementation of ACP in aged-care homes. The Respecting Patient Choices Program piloted a training and implementation model in 19 aged-care homes in Victoria, Australia in 2010-11. The model required selected aged-care home nurses and management staff to attend 3 workshops over a 6-month period and complete pre and post-workshop tasks. The workshops included didactic and experiential teaching, discussions and role plays. Model evaluation included ACP documentation audits, in addition to pre and post implementation surveys to examine aged-care home ACP policies and practices, and staff knowledge, attitudes and behaviours around ACP. Key results were as follows: The available data suggests that the RPC model of ACP in aged-care homes succeeded in training staff and implementing ACP.